2016
DOI: 10.1089/jmf.2015.0123
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Improves Diet-Mediated Recuperation in Rat Model of Nonalcoholic Fatty Liver Disease

Abstract: The aim of the present study was to evaluate the synergic effect of lycopene (LYC) treatment with a dietary control in a nonalcoholic fatty liver disease (NAFLD) model induced with a high-fat diet (HFD). Sprague-Dawley rats were fed during 4 weeks with a normal diet (ND·4w) or an HFD (HFD·4w) to produce an NAFLD model. Then, rats from the ND·4w group continued during 4 weeks with the same diet (ND·8w), and rats from HFD were fed during 4 weeks with an ND (HFD·4w+ND·4w) or an ND plus LYC (HFD·4w+ND+LYC·4w). LYC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 35 publications
5
15
0
Order By: Relevance
“…A recent study used lycopene supplements in Sprague-Dawley rats with high-fat diet-induced NAFLD [76]. The purpose of this study was to assess if lycopene supplementation would have synergistic effects with a control diet in reversing hepatic steatosis and hepatic morphological changes produced by a high-fat diet after NAFLD has developed.…”
Section: Lycopenementioning
confidence: 99%
See 2 more Smart Citations
“…A recent study used lycopene supplements in Sprague-Dawley rats with high-fat diet-induced NAFLD [76]. The purpose of this study was to assess if lycopene supplementation would have synergistic effects with a control diet in reversing hepatic steatosis and hepatic morphological changes produced by a high-fat diet after NAFLD has developed.…”
Section: Lycopenementioning
confidence: 99%
“…Morphological changes observed in the livers of the rats fed a high-fat diet included hepatocyte swelling and macrovesicular steatosis with numerous cytoplasmic vacuoles. The average steatosis score for these animals was significantly higher than that for the rats fed the control diet [76]. …”
Section: Lycopenementioning
confidence: 99%
See 1 more Smart Citation
“…Another study indicates that the antioxidant activity of LYC is mainly dependent on its O 2− and -OH scavenging properties [ 10 ]. Studies have suggested that intake of LYC-enriched food results in many health benefits, such as decreased risks of cardiovascular diseases [ 11 ], nonalcoholic fatty liver disease [ 12 ], malignant brain tumor, brain injury, and other disease [ 13 – 15 ]. The promising effect of LYC on reducing these disease risks is mainly due to the potential of LYC on activating antioxidant enzyme activities and decreasing oxidant productions.…”
Section: Introductionmentioning
confidence: 99%
“…It can reduce high-fat diet-induced steatohepatitis by reducing oxidative stress to the cells. It has been also shown that incorporation of lycopene in balanced diet prevents NAFLD [67,68]. Lycopene may be a useful functional compound for treating NAFLD by regulating hepatic lipid metabolism [69].…”
Section: Lycopene and Chronic Liver Diseasesmentioning
confidence: 99%